2016
DOI: 10.1080/01616412.2016.1187829
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of D-dimer levels with patient outcomes in acute ischemic cerebrovascular disease complicating coronary heart disease

Abstract: AICVD patients complicating CHD is very common in clinical practice. The AICVD patients that complicating CHD showed worse outcomes within 90 days after initial onset of stroke. The D-dimer levels of patients with AICVD complicating CHD were higher. Patients in the CHD group, whose D-dimer levels were higher than the normal standard, had worst outcomes. Paying close attention to the stage of the coronary artery disease and indicators of the coagulation-fibrinolysis is beneficial in the optimization of the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…A Canadian study by Kim et al [37] reported the prognostic value of plasma D-dimer level in patients with noncardioembolic stroke. In a study of a Chinese population with complicating coronary heart disease, the result indicated that higher plasma D-dimer levels had a worse outcome within 90 days after the initial onset of AIS [38]. A Swiss study by Hsu et al reported that a high plasma D-dimer levels indicates an unfavorable outcome in patients with AIS receiving intravenous thrombolysis [39].…”
Section: Discussionmentioning
confidence: 99%
“…A Canadian study by Kim et al [37] reported the prognostic value of plasma D-dimer level in patients with noncardioembolic stroke. In a study of a Chinese population with complicating coronary heart disease, the result indicated that higher plasma D-dimer levels had a worse outcome within 90 days after the initial onset of AIS [38]. A Swiss study by Hsu et al reported that a high plasma D-dimer levels indicates an unfavorable outcome in patients with AIS receiving intravenous thrombolysis [39].…”
Section: Discussionmentioning
confidence: 99%
“…If the plasma D-dimer test is negative, the diagnosis of acute VTE can be ruled out; if the plasma D-dimer test is positive, the diagnosis of VTE can be con rmed by the symptoms and an ultrasound examination 8 . There have also been many relevant studies in some cardiovascular diseases, such as atrial brillation [18][19][20] , coronary heart disease 13,21,22 , stroke 23,24 and aortic dissection [25][26][27] , and D-dimer can even be used as a predictor of the diagnosis and prognosis of such diseases [28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer has been widely used in the diagnosis of VTE 8 , 17 , 18 . There have also been many relevant studies in some cardiovascular diseases, such as atrial fibrillation 19 21 , coronary heart disease 14 , 22 , 23 , stroke 24 , 25 and aortic dissection 26 – 28 , and D-dimer can even be used as a predictor of the diagnosis and prognosis of such diseases 29 32 .…”
Section: Discussionmentioning
confidence: 99%